Inductive Top-Down Theorizing: A Source of New Theories of Organization - Shepherd, Dean A.; Sutcliffe, Kathleen M. (Academy of Management Review, 2011)
Building on coherence theory and a pragmatist tradition, we offer an inductive model of top-down theorizing that can be a source of new theories of organization. We explain how an initial hypothesis is refined to enhance its potential contribution (consistent with abduction). But, unlike abduction, we explain how inquiry begins— how research tensions are carved out of the flux of the vast literature—and how constant comparison facilitates an abductive process.